The giver - Lowry, Lois
Life in the community where Jonas lives is idyllic. Designated birthmothers produce newchildren, who are assigned to appropriate family units: one male, one female, to each. Citizens are assigned their partners and their jobs. No one thinks to ask questions. Everyone obeys. The community is a precisely choreographed world without conflict, inequality, divorce, unemployment, injustice... or choice. Everyone is the same. Excepto Jonas. At the Ceremony of Twelve, the community's twelve-year-olds eagerly accept their predetermined Life Assignments. But Jonas is chosen for something special. He begins instruction in his life's work with a mysterious old man known only as The Giver. Gradually Jonas learns that power lies in feelings. But when his own power is put to the test -when he must try to save someone he loves- he may not be ready. Is it too soon? Or too late?.